A population-based matched cohort study of early pregnancy outcomes following COVID-19 vaccination and SARS-CoV-2 infection - Calvert, Clara; Carruthers, Jade; Denny, Cheryl; Donaghy, Jack; Hillman, Sam; Hopcroft, Lisa E. M.; Hopkins, Leanne; Goulding, Anna; Lindsay, Laura; McLaughlin, Terry; Moore, Emily; Pan, Jiafeng; et al. (Nature communications, 2022)
Data on the safety of COVID-19 vaccines in early pregnancy are limited. We conducted a national, population-based, matched cohort study assessing associations between COVID-19 vaccination and miscarriage prior to 20 weeks gestation and, separately, ectopic pregnancy. We identified women in Scotland vaccinated between 6 weeks preconception and 19 weeks 6 days gestation (for miscarriage; n = 18,780) or 2 weeks 6 days gestation (for ectopic; n = 10,570). Matched, unvaccinated women from the pre-pandemic and, separately, pandemic periods were used as controls. Here we show no association between vaccination and miscarriage (adjusted Odds Ratio [aOR], pre-pandemic controls = 1.02, 95% Confidence Interval [CI] = 0.96–1.09) or ectopic pregnancy (aOR = 1.13, 95% CI = 0.92–1.38). We undertook additional analyses examining confirmed SARS-CoV-2 infection as the exposure and similarly found no association with miscarriage or ectopic pregnancy. Our findings support current recommendations that vaccination remains the safest way for pregnant women to protect themselves and their babies from COVID-19. Data on the safety of COVD-19 vaccines in early pregnancy are limited. Here, the authors assess the rates of miscarriage and ectopic pregnancy following vaccination using electronic health record data from Scotland, and find no evidence of increased risks.